Polatuzumab vedotin plus bendamustine and rituximab in patients with relapsed/refractory diffuse large B‐cell lymphoma in the real world. (11th May 2022) - Vodicka, Prokop; Benesova, Katerina; Janikova, Andrea; Prochazka, Vit; Belada, David; Mocikova, Heidi; Steinerova, Katerina; Duras, Juraj; Karban, Josef; Hanackova, Veronika; Sykorova, Alice; Obr, Ales; et al.
Abstract: Objectives: Polatuzumab vedotin with bendamustine and rituximab (Pola‐BR) was approved for treatment of transplant‐ineligible patients with relapsed/refractory DLBCL (R/R DLBCL). However, the number of patients treated in the GO29365 trial including the extension cohort was limited, and more data evaluating the efficacy of this treatment regimen is needed. Methods: We analyzed 21 patients with R/R DLBCL to determine real‐life efficacy and safety of Pola‐BR regimen. Data of all patients entered the database of the NiHiL project (NCT03199066). Results: Median overall survival was 8.7 months, and progression‐free survival 3.8 months. The overall response rate was 33%. Grade 3–4 neutropenia was detected in 29%, thrombocytopenia in 38%, anemia in 19%, infections in 24% cases, and peripheral neuropathy in 5%. Discontinuation of treatment was caused by progression in 50%, adverse events in 31%, and intended bridging to CAR‐T therapy in 19%. Conclusion: Although the outcome of patients is worse than in GO29365 trial, the use of Pola‐BR regimen in the real world demonstrates tolerable toxicity profile and efficacy in transplant‐ineligible patients with R/R DLBCL. Moreover, this regimen might represent a perspective option as a bridge to CAR‐T therapy.